The Effect of Experimental Methods on Understanding the Use of Science in Elementary Schools - Hamna; Rindiani; Siti Hana; Sulistiyawati (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to examine the impact of the application of experimental methods on improving the understanding of science concepts in elementary school students. The basis for implementing this study is based on the fact that science learning in elementary schools is still dominated by a theoretical and teacher-centered approach, resulting in students being less actively involved in the learning process. The experimental approach was implemented through a simple activity called